Palaeolithic Pioneers - Walker, Michael J. (Archaeopress, 2017)
Archaic humans were present for over a million years in western Mediterranean Europe where they left very many traces of their early stone-age activities and behaviour, and sometimes even human skeletal remains. This book evaluates archaeological findings about their life-ways at many important sites in Italy, southern France, and Spain.